Penerapan Teori Kedaulatan Rakyat Di Indonesia Dalam Sistem Kekerabatan Dalam Pemerintahan Daerah - Yulius Efendi (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2023)
Sovereignty is the highest power to determine the laws in the country. Sovereignty comes from the English "sovereignity", in French it is called "souverainete", and in Italian it is called "sovranus". The origin of the word comes from the Latin superanus which means the highest (supreme). Ahead of the 2024 simultaneous elections, the phenomenon of political dynasties or kinship systems has become an issue that is widely discussed because many candidates are running and have kinship relations with the authorities, however, in the constitutional system this is normal and legal after the Constitutional Court's decision in the judicial review of Law no. 8 of 2015 concerning Regional Elections in letter r. This means that everyone can take part in regional head elections and general elections as long as they have the ability and capacity as a leader and do not just rely on popularity alone and the family that is in power or holding office at both the central and regional levels. (President, Governor to regent/mayor).